RESEARCH OF H-METHODS FOR STABILIZATION OF INFORMATION-MEASURING DEVICES - Сущенко, О.А. (Proceedings of National Aviation University (archive), 2012)
The paper is devoted to research of the modern methods for the wide class control systems robust controllers H-synthesis. The classification of these methods was defined in the paper. The comparative analysis of their possibilities for information-measuring stabilization systems design was carried out. The research results are of interest of the field of the information-measuring stabilization systems assigned for exploitation at the vehicles of the wide class.